COMMUNICATIVE TECHNIQUES OF TEACHING A FOREIGN LANGUAGE. - Zakirova Diloram Yuldashevna, Nazarova Sayyora Azimjanovna, Musadjanova Gulchekhra Abdumanapovna, Sadirova Dinara Sadikovna, Djumaniyazova Malokhat, Suyerova Nursuluv Xusanovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The article examines the teaching of oral communication as one of the most pressing problems of modern methods. Communication in psychology is characterized as a set of social ties, a means of dynamic interaction between society and the individual, as a directly experienced reality. Teaching students to communicate in a foreign language in the context of the educational process is a rather difficult task. After all, natural speech is stimulated not by necessity, but by the need for real communication. Usually, in foreign language lessons, individual or paired forms of work, represented by the monologue or dialogical speech of students, prevail. Communication is carried out mainly within the framework: teacher - student, teacher - class, student - student. However, in natural communicative situations, a person often encounters a polylogical form of communication than a dialogical one: we communicate with members of our family, with classmates, with friends in training, competitions, in clubs of interest, etc. Therefore, teaching group interaction in a foreign language lesson should become a natural component of the educational process.